Pengaruh Tingkat Pendidikan, Pelatihan, dan Pengalaman Mengajar terhadap Profesionalisme Guru Sekolah Dasar Negeri Cemplang Kecamatan Cibungbulang Kabupaten Bogor - Desy Laelasari; Qowaid Qowaid; Efrita Norman (Jurnal Dirosah Islamiyah, 2020)
ABSTRACT The teacher is a professional profession in which he is required to make every effort to carry out his profession as well as possible. Teachers need positions or professions that require special expertise. This work cannot be done by someone who does not have the expertise to carry out activities or work as a teacher. Expertise as a professional teacher must master the ins and outs of education and teaching with a variety of other sciences. This study uses a quantitative method, which is a research method in which data is scored into numbers (quantitative) in the collection and analysis of data. Data collection using research instruments, namely questionnaires. Analysis of quantitative / statistical data with the aim of testing hypotheses Data in quantitative research is in the form of numbers (scores, rankings, or frequencies), the data is then analyzed using statistics in order to answer specific research questions or hypotheses, and to make predictions that an variables affect each other. The results showed that: 1) there was a positive influence of education on teacher professionalism with a significance value obtained less than 0.05 (0.046 <0.05). 2) there is a positive effect of training on teacher professionalism with a significance value of 0.036 because the significance price obtained is less than 0.05 (0.036 <0.05). 3) there is a positive influence of teaching experience on teacher professionalism with a significance value of 0.028 because the significance price obtained is less than 0.05 (0.028 <0.05). 4) there is a positive influence of education, training and teaching experience on the professionalism of teachers at SDN Cemplang 1.3 and 4 Cibungbulang District, Bogor Regency with an F-count = 28,925. Because Fcount> F-table or 28.925> 2.88, Ho is rejected. So, it can be concluded that education, training, and teaching experience together significantly influence the professionalism of teachers in SDN Cemplang 1.3 and 4, Cibungbulang District, Bogor Regency. Keywords: education, training, teaching experience, teacher professionalism